Content of sea grapes (Caulerpa racemose) which grow in the waters of The Button Strait and The Tiworo Strait - Anshar, Anshar; Mosriula, Mosriula (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
Sea grapes (Caulerpa racemosa) is a variety of green algae grown in coastal areas with bioactive compounds that have been used by humans as antitumors, antivirals, and antimicrobials. The coastal regions of Lohia district of Muna, including part of Buton Strait, and the western part of Muna district, specifically in the North Tiworo District of Muna West district, which is part of Tiworo Strait, cultivate sea wine. The purpose of this research is to identify the compounds contained in the sea wine grown in the waters of Buton Strait in Muna district, Lohía district, and Tiworo Strait in Muna West District of Tiworo North district. The methods used in this study are observation and determination of the sample take point, sampling, sample preparation, and identification of sample compounds using a spectroscopic photometer. It was found that the samples from the Buton Strait contained saponins, alkaloids, and tannins, with a water content of 15.13%, an ash content of 26.37%, a protein content of 5.24%, a fat content of 0.16%, and carbohydrates making up 53.10%. The samples from the Tiworo Strait, on the other hand, contained saponins, alkaloids, and tannins, with a water content of 15.35%, an ash content of 22.9%, a protein content of 5.20%, a fat content of 0.14%, and carbohydrates making up 56.62%.